Role of Cord Blood Carboxyhemoglobin in Detecting Significant Hyperbilirubinemia in Term Neonates with ABO Alloimmunization - Tıraş, Mahir; Can, Emrah; Hamilçıkan, Şahin (American Journal of Perinatology, 2021)
Objective This study aimed to assess whether cord blood carboxyhemoglobin (COHb) levels in jaundiced term neonates with and without a positive direct Coombs test (DCT) and in healthy controls could be used as a predictor of severe hyperbilirubinemia. The percentage of cord blood COHb should be higher among neonates with Coombs-positive ABO hemolytic disease than among those with Coombs-negative ABO incompatibility and higher than that of ABO-compatible control neonates.Study Design This cross-sectional descriptive study of 198 term neonates comprised three subgroups: group I featured 68 DCT-positive ABO-incompatible neonates (ABO + DCT), group II featured 60 DCT-negative ABO-incompatible neonates with hyperbilirubinemia (ABO–DCT), and group III featured 70 healthy controls. COHb was determined by an OSM3 hemoximeter.Results Group I differed from groups II and III for cord blood bilirubin, cord blood hemoglobin, and cord blood hematocrit. Groups I and II had higher mean total serum bilirubin (TSB) levels than group III, while there was no difference in the mean TSB levels between groups I and II. There was no significant difference between the COHb group means for groups I, II, and III (p = 0.98). The area under the receiver operating characteristic curve calculated for group I/group III and group II/group III were found to be 0.62 and 0.54, respectively.Conclusion COHb levels did not prove to be superior to the DCT for predicting the risk of developing severe hyperbilirubinemia in term neonates.Key Points
Keywords: ABO incompatibility; carboxyhemoglobin; direct Coombs test; hyperbilirubinemia; neonate